Food Metaphor In The Life Of The Protagonist Aruna And Her Tongue In The Novel "Aruna Dan Lidahnya' By Lasmi Pamuntjak - Celvin Reindira Alfiani; Ari Ambarwati (EDUTEC : Journal of Education And Technology, 2023)
This research focuses on the types of food metaphors that are closely related to the lives of the characters in the novel Aruna and her Tongue. Studies on the novel Aruna and her Tongue have never discussed food metaphors, so this research is important to provide readers with an understanding of examples of food metaphors in the novel Aruna and her Tongue. The research data used is in the form of narrative quotations contained in the novel. This research belongs to descriptive qualitative research. This research aims to describe the metaphorical language style of gastronomic studies contained in the novel Aruna and her Tongue. The data source in this research is dialog or narration of metaphorical language style contained in the novel. Data collection is done by reading the novel, marking technique, dialog or narration that is considered as metaphorical language style in the novel, recording technique, classifying and giving code to the data. The results of this study show that there is a metaphorical language style in the novel Aruna and Lidahnya by Lasmi Pamuntjak. The function of metaphorical language style in the novel is to describe and animate the atmosphere and characters in the story, and also provide an aesthetic touch that enriches the reader's experience with the use of beautiful comparisons and arouses the reader's imagination.